The Effects of Angiogenic Growth Factors on Extravillous Trophoblast Invasion and Motility - Lash, G.E; Cartwright, J.E; Whitley, G.St J; Trew, A.J; Baker, P.N (Placenta (Eastbourne), 1999)
There is accumulating evidence that deficient trophoblast invasion of the placental bed spiral arteries is crucial to the pathogenesis of pre-eclampsia and intrauterine growth restriction. However, the factors which regulate the process of trophoblast invasion remain unclear. We have investigated whether extravillous trophoblast invasion and motility are mediated by the angiogenic growth factors, vascular endothelial growth factor (VEGF) and placental growth factor (PlGF). The SGHPL-4 extravillous trophoblast cell line was utilized. Expression of mRNA for the receptors of VEGF and PlGF (KDR and flt-1) was determined using the reverse transcriptase polymerase chain reaction. An in vitro model of invasion assessed the number and length of trophoblast processes invading into an extracellular matrix. The motility of cells under standard culture conditions was also quantified. The effect of the addition of VEGF and PlGF (±heparin) on trophoblast invasion and motility was determined. The effect of VEGF and PlGF (±heparin) on SGHPL-4 cell proliferation was assessed by cell counts at 24, 48 and 72h post-addition of growth factor. The SGHPL-4 cells expressed mRNA for the flt-1 but not the KDR receptor. The addition of VEGF resulted in a significant decrease in the number of trophoblast processes formed (P< 0.02); this effect was not influenced by the addition of heparin. However, there was no effect on the length of processes formed in response to VEGF (±heparin). The addition of PlGF had no effect on either the number or the length of processes formed. The addition of VEGF increased the motility of the SGHPL-4 cells (P< 0.002); the addition of heparin prevented this VEGF-induced increase in motility. The addition of PlGF had no effect on SGHPL-4 motility (±heparin). Neither growth factor had any effect on the proliferative ability of SGHPL-4 cells. Contrary to our hypothesis, we did not find that the angiogenic growth factors, VEGF and PlGF, mediated the in vitro invasion of trophoblast cells into an extracellular matrix. However, VEGF did increase trophoblast motility. Our findings of an effect of VEGF on trophoblast motility (and possibly invasion) suggests the presence of functional receptors, which can mediate the actions of VEGF. Caution must be exercised before any extrapolation to the in vivo situation, however, it could be speculated that the increased motility in response to VEGF may be an initial response to attract trophoblast cells to the decidua, and that VEGF might then limit the degree to which trophoblast cells invade.